Trajectory and risk factors for chemotherapy‐induced nausea and vomiting in Asian patients with head and neck cancer. Issue 9 (21st July 2014) - Chan, Alexandre; Shwe, Maung; Gan, Yanxiang; Yap, Kevin; Chew, Lita; Lim, Wan–Teck
Abstract Background The purpose of this study was to analyze the trajectory of and risk factors for chemotherapy‐induced nausea and vomiting in Asian patients with head and neck cancer. Methods Adult patients with head and neck cancer scheduled to receive cisplatin‐based chemotherapy were recruited for the study. Clinical events were collated from standardized diaries. Results Two hundred thirty‐five patients were included in the analyses. The majority (75.7%) was men, Chinese (81.7%), and manifested nasopharyngeal cancer (83.4%). The overall incidence of significant nausea and vomiting was 73.7% and 24.7%, respectively, with single‐day cisplatin regimens of 48.9% and 28.9%, respectively, with the multiple‐day cisplatin regimen. Patients using complementary alternative medicine were less likely than others to achieve a complete response to antiemetics. Conclusion Although postchemotherapy vomiting is relatively well controlled in Asian patients with head and neck cancer, postchemotherapy nausea remains problematic in this population. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1349–1357, 2015